2018
DOI: 10.1002/da.22776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insomnia treatments on depression: A systematic review and meta-analysis

Abstract: These results support that treating insomnia in patients with depression has a positive effect on mood. Future trials are needed to identify the subtypes of patients whose depression improves during treatment with insomnia-specific interventions, and to identify the mechanisms by which treating insomnia improves mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 74 publications
9
102
0
9
Order By: Relevance
“…To the best of our knowledge, this is the first pilot study exploring the genetic contribution of the APLN/APLNR pathway to the susceptibility to depression and anxiety in Chinese patients with CHD. We first found that patients with CHD who experienced insomnia had a high risk of comorbid depression and anxiety, which was consistent with previous findings, demonstrating that insomnia is frequently co-morbid with depression and anxiety (Gebara et al, 2018). Additionally, patients with CHD who has alcohol drinking habits were less likely to have FIGURE 2 | Association of apelin receptor (APLNR) rs9943582 polymorphism with PHQ-9 scores in coronary heart disease (CHD) patients with comorbid depression.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this is the first pilot study exploring the genetic contribution of the APLN/APLNR pathway to the susceptibility to depression and anxiety in Chinese patients with CHD. We first found that patients with CHD who experienced insomnia had a high risk of comorbid depression and anxiety, which was consistent with previous findings, demonstrating that insomnia is frequently co-morbid with depression and anxiety (Gebara et al, 2018). Additionally, patients with CHD who has alcohol drinking habits were less likely to have FIGURE 2 | Association of apelin receptor (APLNR) rs9943582 polymorphism with PHQ-9 scores in coronary heart disease (CHD) patients with comorbid depression.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, meta-analyses of RCTs also support the efficacy of sleep interventions in reducing symptoms of depression. Of note, whereas many trials have shown the alleviation of subclinical depressive symptoms following sleep interventions, the available evidence suggests that even larger effects of sleep therapies on depression are observed in those with mental illness [79][80][81]94 . Additionally, a role of poor sleep in severe mental disorders is suggested by a recent RCT showing that CBT for insomnia (CBT-I) significantly reduces the severity of hallucinations and para-noia in youth experiencing symptoms of psychosis 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, interventions on insomnia also ameliorate depressive symptoms (44, 46, 47, 84, 247, 399) (for meta-analysis, see (139)). While it has been demonstrated that insomnia is indeed an independent risk factor contributing to first onset depression (43), a six month insomnia intervention follow-up was insufficiently sensitive to find differences between treatment and placebo with respect to the incidence of new onset major depressive disorder (84).…”
Section: Mental Health Risks Conveyed By Insomniamentioning
confidence: 99%